Characterization and evaluation of the leachability of bottom ash from a mobile emergency incinerator of COVID-19 medical waste: A case study in Huoshenshan Hospital, Wuhan, China. (1st February 2022) - Miao, Jiahe; Li, Jining; Wang, Fenghe; Xia, Xinyi; Deng, Shaopo; Zhang, Shengtian
Abstract: To dispose of the medical waste generated during the COVID-19 pandemic, a new type of mobile emergency incinerator (MEI) was used in Huoshenshan Hospital, Wuhan, China, and consequently, it produced a number of medical bottom ashs (MBAs). In this study, the characterization and environmental risk evaluation of these MBAs were conducted to evaluate the disposal effect of this MEI used during the pandemic. Three types of leaching tests, EN 12457–2, TCLP 1311, and HJ/T 299–2007, were compared to investigate the release behaviors of major and trace elements from these MBAs. Lack of detection of COVID-19 in MBAs showed that this mobile emergency incinerator could thoroughly eliminate the COVID-19 virus in medical wastes to avoid secondary transmission. The results indicated that the increasing usage of chlorinated disinfectants and physiological saline solutions resulted in high Cl contents in MBAs. In addition, the increasing usage of polypropylene (PP) products changed the chemical properties and compositions of MBAs, with Ca as the main element. The leachability investigation revealed that the main metals in leachates were Ca, Na and K, and the toxic heavy metals such as Zn, Pb, Cu, and Cr in MBAs were difficult to extract because of the high pH (>12) of these MBAs. This study could provide consultation for the treatment and management of MBAs produced from MEIs dealing with emergent infectious diseases such as COVID-19. Graphical abstract: Image 1 Highlights: Characteristics of COVID-19 medical waste bottom ashes from a mobile emergency incinerator were investigated. The increasing usage of chlorinated disinfectant and physiological saline resulted in high Cl contents in MBAs. The increasing usage of polypropylene products increased the Ca in MBAs and reduced the particle size of MBAs. The Ca, Na, and K were dominant while toxic heavy metals were limited in leachates.